Post-traumatic stress disorder as a consequence of bullying at work and at school. A literature review and meta-analysis. (March 2015) - Nielsen, Morten Birkeland; Tangen, Tone; Idsoe, Thormod; Matthiesen, Stig Berge; Magerøy, Nils
Abstract: Bullying has been established as a prevalent traumatic stressor both in school and at workplaces. It has been claimed that the mental and physical health problems found among bullied persons resembles the symptomatology of Post Traumatic Stress Disorder (PTSD). Yet, it is still unclear whether bullying can be considered as a precursor to PTSD. Through a review and meta-analysis of the research literature on workplace- and school bullying, the aims of this study were to determine: 1) the magnitude of the association between bullying and symptoms of PTSD, and 2) whether the clinical diagnosis of PTSD applies to the consequences of bullying. Altogether 29 relevant studies were identified. All had cross-sectional research designs. At an average, 57% of victims reported symptoms of PTSD above thresholds for caseness. A correlation of .42 (95% CI: .36–.48; p  < .001) was found between bullying and an overall symptom-score of PTSD. Correlations between bullying and specific PTSD-symptoms were in the same range. Equally strong associations were found among children and adults. Two out of the three identified clinical diagnosis studies suggested that bullying is associated with the PTSD-diagnosis. Due to a lack of longitudinal research and structural clinical interview studies, existing literature provides no absolute evidence for or against bullying as a causal precursor of PTSD. Highlights: Summarizes research literature on the associations between bullying and PTSD The majority of victims reports symptoms of PTSD. Exposure to bullying is cross-sectionally associated with symptoms of PTSD. No longitudinal studies and few studies with clinical diagnosis It is not possible to determine causal associations between bullying and PTSD based on existing literature.